2021
DOI: 10.1186/s12913-021-06255-0
|View full text |Cite
|
Sign up to set email alerts
|

Health service use of Australian unemployment and disability benefit recipients: a national, cross-sectional study

Abstract: Background Healthcare is funded and delivered separately from income support programs such as unemployment and disability benefits. Greater understanding of the health service use (HSU) of benefit recipients would support more effective design and delivery of health and income support programs. This study aimed to characterise the HSU of disability and unemployment benefit recipients relative to people earning wages, while controlling for personal, household and health-related factors associate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
(7 reference statements)
1
10
0
Order By: Relevance
“…In an Australian study, patients receiving disability pension or unemployment benefits had no differences in hospital use compared with wage-earning patients. 34 A Danish study reported that job loss from plant closure was not associated with an increase in all-cause hospitalization, but there was an increase in hospitalization from alcohol-related diseases. 35 International studies are often difficult to compare, however, because unemployment laws and medical benefits can be markedly different from country to country.…”
Section: Discussionmentioning
confidence: 99%
“…In an Australian study, patients receiving disability pension or unemployment benefits had no differences in hospital use compared with wage-earning patients. 34 A Danish study reported that job loss from plant closure was not associated with an increase in all-cause hospitalization, but there was an increase in hospitalization from alcohol-related diseases. 35 International studies are often difficult to compare, however, because unemployment laws and medical benefits can be markedly different from country to country.…”
Section: Discussionmentioning
confidence: 99%
“…There are also gaps in health service delivery. For example one study of disability pension recipients identified that although 69% reported a diagnosed mental health problem, only 16% reported receiving specialist mental health care [8], a finding reflected in similar studies of workers' compensation cohorts [3,10].…”
Section: Introductionmentioning
confidence: 93%
“…Common diseases and illnesses of working age are the major causes of work disability, and include conditions with high prevalence such as low back pain, depression, anxiety, traumatic injury, as well as cancers and circulatory system disorders [1,2] The consequences of work disability can be significant for workers. People with prolonged work disability suffer worse mental health [3][4][5], have shorter life expectancy [6], attend healthcare consultations more frequently with physical symptoms and report higher levels of pain [7], receive more social care [8], and report reduced quality of life [9]. There are also gaps in health service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Social support is a protective factor that reduces the risk of suicide death in adults (20) that may be adversely impacted during periods of work disability. Finally, many people with work disability and concurrent mental health problems do not receive appropriate mental health treatment, and thus the risk of self-harm or future suicide is more likely to go unrecognised (2,7).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of work disability can be significant for workers. People with prolonged work disability suffer worse mental health (2)(3)(4), have shorter life expectancy (5), attend healthcare consultations more frequently with physical symptoms and report higher levels of pain (6), receive more social care (7), and report reduced quality of life (8). There are also gaps in health service delivery.…”
Section: Introductionmentioning
confidence: 99%